PENGARUH BUDAYA KERJA, PELATIHAN, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DITRES NARKOBA POLDA SUMUT - Hartati, Rini; Utama, Indra; Hidayat, Toni; Rahmat, Muhammad (Universitas Dharmawangsa, 2024)
This study aims to determine the impact of work culture, training, and job satisfaction on employee performance at the Narcotics Directorate of the North Sumatra Regional Police. This research is associative with a quantitative approach. The sample in this study consisted of 116 employees from the Narcotics Directorate of the North Sumatra Regional Police. The analysis technique used is multiple linear regression analysis. The results of this study show that work culture has a positive and significant effect on employee performance at the Narcotics Directorate of the North Sumatra Regional Police. Training has a positive and significant effect on employee performance at the Narcotics Directorate of the North Sumatra Regional Police. Job satisfaction has a positive and significant effect on employee performance at the Narcotics Directorate of the North Sumatra Regional Police. Work culture, training, and job satisfaction have a positive and significant effect on employee performance at the Narcotics Directorate of the North Sumatra Regional Police.